NURSES RESPONSE TIME IN EMERGENCY HANDLING OF PATIENTS WITH HIGH PRIORITY CATEGORIES: A LITERATURE REVIEW - Sugito Tri Gunarto; Rondhianto Rondhianto; Dodi Wijaya (UNEJ e-Proceeding, 2023)
Background: The patient mortality rate in the emergency department indicates the quality of patient care. One of the contributing factors is the nurse's response time in providing services to patients. Service delays can cause increased mortality in patients with high-priority categories. The purpose of this research is to identify how the response time of nurses in serving high-priority patients, the impact and causal factors, and strategies to improve nurse response time behavior. Methods: a systematic review using the PRISMA protocol and the JBI Critical Appraisal Tool was used to determine eligible articles. Articles were sourced from four electronic databases (Scopus, PubMed, Science Direct and Google Scholar). The inclusion criteria include research on the response time of nurses to patients in the emergency department, published in English in the last five years (2019 - 2023). Result: 19 articles were obtained according to the criteria. The analysis showed an increased risk of death in patients with the highest priority triage level, and an increase in response time positively impacted reducing the risk of death. Factors influencing response time behavior include age, gender, education level, length of work, knowledge, training, skills, self-efficacy, and work motivation. Conclusion: Efforts to increase response time are one factor in reducing the risk of death in patients with high priority. Strategies to improve nurse response time behavior in emergency services must consider factors influencing behavior to improve emergency services and reduce the risk of death.